2019
DOI: 10.1007/s00217-019-03284-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of triticale malt application on physiochemical composition and profile of volatile compounds in beer

Abstract: In brewing industry, adjuncts may replace malt, but they may also represent a raw material for brewing beer demonstrating different, specific organoleptic qualities. Triticale grain may give good quality malts, characterised by high extraction capacity, high diastatic power and short saccharification time. The purpose of the research was to determine the impact of triticale malt application on physiochemical composition and profile of volatile compounds in beer. In fermented wort, the content of ethyl alcohol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…Among those, Tritordeum (x Tritordeum martinii), obtained by crossing wild barley with wheat, was comparable to barley in saccharification time, lautering, as well as colour and turbidity, but a slightly acidifying effect and higher free amino nitrogen were observed [22]. Whereas, Triticale (x Triticosecale), a hybrid of durum wheat and rye, is suitable for malt production because of its high extraction capacity, high diastatic power, and short saccharification time, but with higher acidity and lower esters and isoamyl alcohol content [23].…”
Section: Grains and Malted Cerealsmentioning
confidence: 91%
“…Among those, Tritordeum (x Tritordeum martinii), obtained by crossing wild barley with wheat, was comparable to barley in saccharification time, lautering, as well as colour and turbidity, but a slightly acidifying effect and higher free amino nitrogen were observed [22]. Whereas, Triticale (x Triticosecale), a hybrid of durum wheat and rye, is suitable for malt production because of its high extraction capacity, high diastatic power, and short saccharification time, but with higher acidity and lower esters and isoamyl alcohol content [23].…”
Section: Grains and Malted Cerealsmentioning
confidence: 91%
“…They owe their popularity largely to their wide variety and original styles on offer. Frequently, in an effort to develop interesting beer flavors, sugar sources other than barley malt are used (e.g., lentil [4], buckwheat [5], triticale [6], oats [7], black rice [8]). Another method of influencing organoleptic characteristics is through enriching beer with new, herb-derived aromas, as well as other aromas originating from biological materials [9].…”
Section: Introductionmentioning
confidence: 99%
“…e higher FAN content of quinoa (283 mg/L) was reported in a study [12], with FAN in the range of 170-200 mg/L reported elsewhere [46][47][48]. In a related study, the FAN content of triticale malt (a cross-breed of wheat and rye) was lower (170 mg/l) in comparison with barley malt (210 mg/L) [49].…”
Section: Effect Of Steeping Time and Germinationmentioning
confidence: 81%